Allergies, away! : creative eats and mouthwatering treats for kids allergic to nuts, dairy, and eggs - Park, Ginger (Thomas Dunne Books, St. Martin's Griffin, 2013)
"When sisters Ginger and Frances Park opened up a chocolate shop in Washington, D.C., they couldn't wait to share their gourmet sweets with their friends and family. Unfortunately, Ginger's son, Justin, was born with severe food allergies, and even visiting the shop-made Justin sick. Far from discouraged, Ginger and Frances vowed they would find alternatives for Justin that tasted better than the real thing. Inspired by their mission, Frances and Ginger wrote Allergies, Away!, a fun and healthy cookbook chock full of recipes for the millions of parents whose children have food allergies. This book features more than seventy-recipes for-kid-friendly foods like Seoulful Half-Moon Dumplings, Rock Star Onion Rings, and Orange Chocolate Muffins, and every recipe is free of dairy, nuts, and eggs. The recipes are easy enough to make with children, and Frances and Ginger include helpful tips for maximum fun in the kitchen. Perfect for parents who are sick of making bland and boring food for their allergic kids, Allergies, Away! is the ultimate guide to tasty,-homemade food that is also allergen-free"--